Los Artesanos’ Neighborhood Hability Conditions, La Libertad City in Velasco Ibarra Sector, Santa Elena - Ecuador, 2022 - Garzozi-Pincay René Faruk; Garzozi-Pincay Yamel Sofia; Pinargote-Guerrero Allison Geomayra; Molina Lilian; Carrera-Garzozi Arturo Francisco (Syntax Corporation Indonesia, 2023)
Household overcrowding is synthesized as a dwelling habitability’s dimension, and it is identified based on bedrooms availability for the number of people who make up the household. However, in this research, the problem is contextualized, giving territory’s details or sector’s study, in addition, international and national organizations are cited that place home overcrowding as a habitability condition necessary to investigate. With this base, the research’s objective is established, which mark the characterizing process household overcrowding. Those, include the situational diagnosis’ development that allows distinguishing the study sector’s housing conditions and in effect generate strategies in accordance with the Territorial Planning Plan to minimize the problem’s progress. The methodological framework is exposed where the type and research scope is detailed, the study population and the information gathering instrument applied and structured based on the variables’ operationalization are established. The data’s quantitative analysis is shown, followed by the discussion process based on the results obtained.